2021
DOI: 10.1371/journal.ppat.1010051
|View full text |Cite|
|
Sign up to set email alerts
|

Polymerization of C9 enhances bacterial cell envelope damage and killing by membrane attack complex pores

Abstract: Complement proteins can form membrane attack complex (MAC) pores that directly kill Gram-negative bacteria. MAC pores assemble by stepwise binding of C5b, C6, C7, C8 and finally C9, which can polymerize into a transmembrane ring of up to 18 C9 monomers. It is still unclear if the assembly of a polymeric-C9 ring is necessary to sufficiently damage the bacterial cell envelope to kill bacteria. In this paper, polymerization of C9 was prevented without affecting binding of C9 to C5b-8, by locking the first transme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…Deposition of C3b on the bacterial surface ( Figure 1b ) and release of C3a in the supernatant ( Figure 1—figure supplement 1b ) were similar on three strains compared to the MAC-sensitive strains, indicating that these strains activate complement efficiently. We have previously shown that MAC components bind to these strains after complement activation ( Doorduijn et al, 2021 ), suggesting that they are ‘MAC-resistant’ strains. The other five strains showed little to no deposition of C3b and were considered ‘complement-resistant’.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deposition of C3b on the bacterial surface ( Figure 1b ) and release of C3a in the supernatant ( Figure 1—figure supplement 1b ) were similar on three strains compared to the MAC-sensitive strains, indicating that these strains activate complement efficiently. We have previously shown that MAC components bind to these strains after complement activation ( Doorduijn et al, 2021 ), suggesting that they are ‘MAC-resistant’ strains. The other five strains showed little to no deposition of C3b and were considered ‘complement-resistant’.…”
Section: Resultsmentioning
confidence: 99%
“… Escherichia. coli strains ( a ) and Klebsiella strains ( b ) were typed for the presence of LPS O-Ag via silver staining (methods described in Doorduijn et al, 2021 ). LPS-core were distinguished from LPS O-Ag based on size.…”
Section: Resultsmentioning
confidence: 99%
“…MAC is a multiprotein pore whose oligomerization occurs by sequential addition of C5b, C6, C7, C8 and finally C9 which forms an oligomeric ring of 18 units inserted into bacterial membranes (Bayly-Jones, Bubeck and Dunstone, 2017). Although the composition of MAC has been known for years, its contribution to bacterial cell death and the way the bacteria die upon MAC insertion is still a debate (Doorduijn, Rooijakkers and Heesterbeek, 2019), and recent work suggested that complement-resistant bacteria can specifically block polymerization of C9 (Doorduijn et al, 2021). SrgA is a protein of 7.1 kDa after predicted signal peptide cleavage, probably localized in the bacterial periplasm and/or exported to the bacterial surface.…”
Section: Discussionmentioning
confidence: 99%
“…While the pores formed by the C5b-8 complex are unstable and short-lived, they can kill nucleated cells (Tegla et al, 2011). However, the relatively more stable tubular structure of the C5b-8,9n complex is required to kill gram-negative bacteria and is the target of complement evasion strategies of specific pathogens (Doorduijn et al, 2021(Doorduijn et al, , 2020Joiner, 4 1988;Zhao et al, 2014). The C9-mediated killing of bacteria in the absence of C5b-8 has also been reported (Dankert and Esser, 1987).…”
Section: Introductionmentioning
confidence: 98%